2015
DOI: 10.1186/s12864-015-2082-3
|View full text |Cite
|
Sign up to set email alerts
|

New global analysis of the microRNA transcriptome of primary tumors and lymph node metastases of papillary thyroid cancer

Abstract: BackgroundPapillary Thyroid Cancer (PTC) is the most prevalent type of endocrine cancer. Its incidence has rapidly increased in recent decades but little is known regarding its complete microRNA transcriptome (miRNome). In addition, there is a need for molecular biomarkers allowing improved PTC diagnosis.MethodsWe performed small RNA deep-sequencing of 3 PTC, their matching normal tissues and lymph node metastases (LNM). We designed a new bioinformatics framework to handle each aspect of the miRNome: whole exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 66 publications
7
63
2
1
Order By: Relevance
“…To ensure the quality of these RNA editing hotspots, we further ruled out the possibility of any unreported SNPs and somatic mutations or cross-mapping (Methods). Among these editing hotspots, 18 (95%) are located at the position 1-8 of mature miRNAs, 12 (63%) have been reported in previous studies (Blow et al 2006;Kawahara et al 2007aKawahara et al ,b, 2008Alon et al 2012;Choudhury et al 2012;Gong et al 2014;Warnefors et al 2014;Saiselet et al 2015;Tomaselli et al 2015;Nishikura 2016), and two editing sites (miR-151a and miR-376a) have been functionally characterized (Kawahara et al 2007a;Choudhury et al 2012). To further characterize these miRNA editing hotspots, we calculated their editing frequency (defined as the fraction of the tumor samples with detectable editing signals), the edited miRNA expression amount (defined as the RPM), and the editing level across cancer types.…”
Section: Systematic Detection Of Rna Editing Hotspots In Mirnas Acrosmentioning
confidence: 97%
“…To ensure the quality of these RNA editing hotspots, we further ruled out the possibility of any unreported SNPs and somatic mutations or cross-mapping (Methods). Among these editing hotspots, 18 (95%) are located at the position 1-8 of mature miRNAs, 12 (63%) have been reported in previous studies (Blow et al 2006;Kawahara et al 2007aKawahara et al ,b, 2008Alon et al 2012;Choudhury et al 2012;Gong et al 2014;Warnefors et al 2014;Saiselet et al 2015;Tomaselli et al 2015;Nishikura 2016), and two editing sites (miR-151a and miR-376a) have been functionally characterized (Kawahara et al 2007a;Choudhury et al 2012). To further characterize these miRNA editing hotspots, we calculated their editing frequency (defined as the fraction of the tumor samples with detectable editing signals), the edited miRNA expression amount (defined as the RPM), and the editing level across cancer types.…”
Section: Systematic Detection Of Rna Editing Hotspots In Mirnas Acrosmentioning
confidence: 97%
“…Consequently, the discrepant results between studies could be due to the absence of specific miRNAs in some profiling platforms. miR-204-3p and miR-7-3p are examples of such miRNAs: their expressions have been reported as decreased in PTC in recent small RNA deep sequencing studies [18, 19] but these miRNAs are absent from the microarray platform used in a study using similar samples in 2011 [22]. Actually, miR-204-3p is still missing in more recent microarrays platforms [29, 30].…”
Section: Differential Expression Profilingmentioning
confidence: 99%
“…Since then, the field has been improved by the release of new miRNA functional and expression profiling studies. Next generation sequencing (small RNA deep sequencing technologies) gives a new reading of miRNA differential expression profiles of PTC and FTC [1319]. …”
Section: Introductionmentioning
confidence: 99%
“…Many publications have reported that PTC samples with different degrees of aggressiveness present different microRNA expression profiles, on the basis of microarrays and qRT-PCR analyses. These studies revealed the common up-regulation of the wellcharacterized miR-146b-5p, miR-221-3p and miR-222-3p in aggressive PTC compared to non-aggressive samples but no commonly down regulated microRNAs [24]. Through to investigations, it was revealed that miRNAs found in the exosomes are associated with a variety of specific diseases such as cancer, for example, research has shown that exosomes in blood circulation are similar to exosomes in the origin of their cancer cells.…”
Section: Discussionmentioning
confidence: 96%
“…Four were down-regulated (miR-122, miR-183, miR-149, and miR514a) and seven were up-regulated (miR-146b, miR-222, miR-221, miR-10b, miR-199a/miR-199b, miR-203 and miR-32) [23,24]. MiR-221, miR-222 and miR-146b were also up-regulated in experimental models of thyroid tumorigenesis [16,25].…”
Section: Discussionmentioning
confidence: 99%